Redes: difusão do conhecimento e controle - um estudo de caso na indústria brasileira de caminhões. - Sacomano Neto, Mário (Universidade Federal de São Carlos, 2004)
This research has compared the coordination and relation structures in two truck manufactures in Brazilian automotive industry. The network analysis level has been consolidated as an adequate approach in order to understand the cooperation/competition binomial, which involves the markets and the relationship among economic actors. In the network analysis, it has been assumed that the environment in which the organizations work is structured by technological and productive vehicles, established between companies and institutions. Within the field of economic sociology and the organization theory there is an increasing concern in order to understand how a structural position and the type of relationship among the economic actors in a certain network have influenced the organization performance and its strategic behavior. Over the last decade, it has been observed a deep structural change within the Brazilian automotive section, with direct consequences in the suppliers network. The direct consequence of this change is the set of opportunities that truck manufactures and autopart suppliers can obtain from their relational and structural positions within the Brazilian automotive sector. The central issue of this work is related to how the different relational and structural positions of the autopart suppliers in the automobile network influence the diffusion levels of knowledge, the truck manufacture control over the suppliers and their relationship of power. The conclusions of this research have revealed that the cohesive and dense relationship has great possibilities to promote diffusion channels between truck manufacture and autoparts in order to generate distinctive and highly institutionalized control structures on the suppliers and, also to redistribute the power of decision to autopart suppliers.
Keywords: Organização da produção; Análise de redes (planejamento); Configuração das redes; Estrutura de coordenação; Enredamento; Indústria automotiva; Network analysis; Network configuration; Structural and relational position; Coordination structure; Embeddedness; Automobile industry; ENGENHARIAS::ENGENHARIA DE PRODUCAO